Character Education Application in Thematic-Integrative Learning of Curriculum 2013 - Hani Dwi Hastuti; Marsigit Marsigit (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2020)
This research development aims to produce thematic-integrative teaching materials based on a scientific approach. The product produced aims to develop a confident character. Teaching materials developed get positive responses from students with excellent task completion achievement, amounting to 81.5%. This is evidenced based on the results of expert assessments which show that teaching material developed from the aspect of content eligibility is categorized as